The Effect of Using AI Applications in Improving English Reading Skills of Students at MA Al Ishlahiyah Binjai - Asmayani, Asmayani; Tanjung, Alfian; Piliang, Fenny Mustika (Lembaga Riset Mutiara Akbar, 2024)
This research is quantitative research. The population in this research is the entire population in the research is all MA Al Islahiyah Binjai students, totaling 140 people. The sample in the research refers to an error level of 5%. The sample in this study was 100 people. The variables in this research consist of AI applications as variable X and students' English reading ability as variable Y. The research results show that (1) The percentage value of students' AI applications at MA Al Islahiyah Binjai is P = 84.4%. Based on the results obtained above, it can be seen that the AI application at MA Al Islahiyah Binjai can be said to be very, very good. (2) The percentage value of English reading ability is 83.07%. Based on the results obtained above, it can be seen that the English reading ability of students at MA Al Islahiyah can be said to be very good. (3) There is a significant influence between AI applications on students' English reading ability at MA Al Islahiyah Binjai with Adjusted R Square 0.822 meaning 82.2%. Meanwhile, 17.8% (100%-82.2%) was explained by other factors not examined by researchers. Based on this research, it shows that the t-count value of the AI application variable is 11.633, which is greater than t table, namely 2.048 or 11.633 > 2.048 and is significant at 0.000, so it can be concluded that the AI application variable has a significant effect on students' English reading ability at MA Al Islahiyah Binjai because of its significant value. below 0.05.